Extensive Sprouting of Sensory Afferents and Hyperalgesia Induced by Conditional Expression of Nerve Growth Factor in the Adult Spinal Cord - Romero, Mario I. (J Neurosci, 2000)
Genetic transfer of growth-promoting molecules was proposed as a potential strategy to modify the nonpermissive nature of the adult CNS to induce axonal regeneration. To evaluate whether overexpression of neurotrophins or cellular adhesion molecules would effect axonal plasticity, adenoviruses encoding fibroblast growth factor-2 (FGF-2/Adts), nerve growth factor (NGF/Adts), neurotrophin-3, and the cell adhesion molecules N-cadherin and L1 were injected into the dorsal horn of the adult spinal cord. Transgene expression was primarily localized to astrocytes in the dorsal horn and motor neurons within the ventral horn. Overexpression of these factors, with the exception of NGF/Adts, failed to increase axonal sprouting. Eight days after NGF/Adts injections, axonal sprouting within the dorsal horn was apparent, and after 4 weeks, extensive spouting was observed throughout the entire dorsal horn, extending into the ventral horn and the white matter of the lateral funiculus. These axons were identified primarily as a subpopulation of nociceptive fibers expressing calcitonin gene-related peptide and substance-P. Behavioral analysis revealed thermal hyperalgesia and perturbation of accurate paw placement on grid-walking tasks for both FGF-2- and NGF-treated animals. These results indicate that the administration of growth-promoting molecules can induce robust axonal plasticity of normal adult primary sensory neurons into areas of transgene expression, causing significant alterations in behavioral responses. This observation also indicates that gene transfer protocols that aim to reconstruct diseased or injured pathways should also be designed to prevent the sprouting of the normal circuitry from adjacent unaffected neurons.